The Real and the Virtual in the Spatial Perception of Education Students - Bea Tomšič Amon (Center for Educational Policy Studies Journal)
The article presents an investigation conducted with education students at the Faculty of Education, University of Ljubljana. The aim was to determine whether the perception and image of urban space have changed over the years, as the same questionnaire was used in 2001 and 2019. The students had to choose which of the eleven questions contained in the questionnaire they wanted to answer in order to describe their favourite place in the city. Questions that were not significant to them were left unanswered. Here we present a comparison between the results from 2001 and 2019, analysed quantitatively and qualitatively. Despite the fact that spatial perception involves all of the senses, it was the sense of touch, as opposed to vision, that was mentioned the least in both cases. Our original assumption was that with the advance of digital media, perception of real space would be more concise. However, there were a number of students in 2019 who expressed themselves more accurately than those in 2001, suggesting that students have developed a greater sensitivity towards space. The general findings suggest that we should rethink the pedagogical process and some suggestions are presented in the conclusion.